Effect of bracket base design on shear bond strength to feldspathic porcelain - Dalaie, Kazem; Mirfasihi, Armin; Eskandarion, Solmaz; Kabiri, Sattar (European Journal of Dentistry, 2016)
Objectives: This study sought to assess the effect of bracket base design on the shear bond strength (SBS) of the bracket to feldspathic porcelain. Materials and Methods: This in vitro, experimental study was conducted on 40 porcelain-fused-to-metal restorations and four different bracket base designs were bonded to these specimens. The porcelain surfaces were etched, silanized, and bonded to brackets. Specimens were thermocycler, incubated for 24 h and were subjected to SBS. Data were analyzed using Shapiro–Wilk test, Levene's test, one-way ANOVA, and Tukey's honest significant difference test. Adhesive remnant index was calculated and compared using Fisher's exact test. Results: One-way ANOVA showed that the SBS values were significantly different among the four groups (P < 0.001). Groups 1, 2, and 4 were not significantly different, but group 3 had significantly lower SBS (P < 0.001). Fractures mostly occurred at the porcelain-adhesive interface in Groups 1 and 2 while in Groups 3 and 4, bracket-adhesive and mixed failures were more common. Conclusion: The bracket base design significantly affects the SBS to feldspathic porcelain.
Keywords: Bond strength; dental porcelain; orthodontic brackets